Determinants Of Corporate Profit Management In Jakarta Islamic Index Mediated By Company Performance - Emy Widyastuti; Anis Rimba Utami (LPPM ISNJ Bengkalis, 2023)
Corporate earnings management is an essential issue in business entities. The fact reveals that users of financial statements are more focused on what is stated in the financial statements rather than how the profit process is obtained. This study analyzes and shows the factors influencing company earnings management in the Jakarta Islamic Index (JII) for the 2016-2020 period. Company performance is used as an intervening variable. This research uses a quantitative approach with secondary data in the form of panel data. The research population is all companies in the Jakarta Islamic Index (JII) for the 2016-2020 period, namely 30 companies. The sampling technique is purposive sampling, and 13 company samples were obtained. Data analysis technique using multiple linear regression and path analysis. The results showed that the independence of the audit committee, audit committee meetings, and company size positively and significantly affect earnings management. The audit committee size does not affect earnings management. Audit committee independence, audit committee size, and audit committee meeting do not affect company performance. Firm performance cannot mediate the effect of audit committee independence, size, and meetings on earnings management. This research can complement existing theory and be a reference for companies in improving performance and earnings management.